Die medikamentöse Prophylaxe nach elektronischer Kardioversion von chronischem Vorhofflimmern. Ziele und Design der PAFAC-Studie - Fetsch, T; Burschel, G; Breithardt, G; Engberding, R; Koch, H P; Lukl, J; Trappe, H J; Treese, N (Zeitschrift für Kardiologie, 1999)
Atrial fibrillation (AF) is the most frequent cardiac arrhythmia. However, despite manifold publications reflecting numerous clinical trials about treatment of AF, the management of this arrhythmia is still under controversial discussion, in daily clinical work as well as in research. The present study concentrates on three major questions: 1. How frequent are recurrences of AF in long-term follow-up? Most of the previous studies used the occurrence of symptoms as a surrogate parameter for recurrences of AF, despite the expected high rate of asymptomatic relapses. In the present study a daily transtelephonic ECG transmission enables a rhythm monitoring independent of symptoms. 2. Is the frequency of AF recurrences significantly reduced by antiarrhythmic medication? A direct comparison of class I and III antiarrhythmic drugs, which still are most frequently used for this indication, and of placebo will answer this question. 3. How safe is the long-term treatment for the prevention of AF recurrences with special respect to proarrhythmic effects? The daily transtelephonic ECG transmission enables a quantitative and qualitative monitoring of tachy- and bradyarrhythmias independent of symptoms. Additionally, the daily analysis of ECG measures may detect parameters predicting subsequent life threatening arrhythmias. The study design provides a prospective, randomised, double-blind, placebo controlled, multicenter parallel group comparison. In Germany and in the Czech Republic about 90 hospitals will include 900 patients with documented chronic AF, age 18 to 80 years, if they are eligible for electrical cardioversion without concomitant antiarrhythmic drug therapy and if they are anticoagulated for at least three weeks prior to inclusion. Neither the size of the left atrium nor the duration of chronic AF are exclusion criteria. A few hours after successful electrical cardioversion the patients are randomised either to sotalol (2 x 160 mg) or quinidine + verapamil (3 x 160 mg + 3 x 80 mg) or placebo. Starting at the day after cardioversion, the patient is asked to record and transmit electrocardiograms of one minute duration at least once a day using his personal transtelephonic ECG recording unit (Tele-ECG recorder, credit card size), in case of symptoms as often as necessary. The ECGs can be transmitted at any time by any regular phone without additional equipment using a toll free number. A custom made, computer based, fully automated receiving centre is handling the patient calls interactively with voice control, including a voice recording of the patient's symptoms. The ECG tracings and the patient's voice messages are subsequently computer based analysed by experienced technicians. All ECG measures are stored in a database. In case of AF recurrence, any other relevant arrhythmia or additional abnormalities (e.g. QT prolongation) the correspondent hospital is immediately informed by fax. In case of AF recurrence, a subsequent Holter recording discriminates in paroxysmal and permanent AF. Study medication is ended if either permanent AF or the third episode of paroxysmal AF are detected or after 12 months of follow-up. Regular follow-up visits are performed monthly. Major endpoints are the time to first recurrence of AF or the time to death, secondary parameters are the number of AF recurrences, the time to end of medication and AF related symptoms. The recruitment started in the last days of 1996. Until the end of June 1998, 424 patients have been randomised. It is expected to end recruitment in spring 1999 and to close the study in spring 2000. Final results will be available in summer 2000.
Keywords: dospělí; telemetrie; Germany; antiarytmika; Female; elektrokardiografie ambulantní; Atrial Fibrillation; Adult; fixní kombinace léků; ženské pohlaví; elektrická defibrilace; Adolescent; sotalol; lidé; Sotalol; dvojitá slepá metoda; Německo; Electric Countershock; Aged, 80 and over; prospektivní studie; verapamil; Double-Blind Method; Male; Aged; Prospective Studies; Telemetry; Verapamil; Czech Republic; Česká republika; Electrocardiography, Ambulatory; chronická nemoc; fibrilace síní; lidé středního věku; senioři nad 80 let; senioři; mužské pohlaví; chinidin; Anti-Arrhythmia Agents; Chronic Disease; Middle Aged; mladiství; Drug Combinations; Quinidine; Humans